A new species of Cosmolaelaps Berlese (Acari: Laelapidae) from Ukraine - Joharchi, Omid; Trach, Viacheslav A. (Zootaxa, 2019)
This paper reports on a new species of mites of the genus Cosmolaelaps from Ukraine. Cosmolaelaps sidorchukae sp. nov. was collected from unknown ant’s nest. The new species is described and illustrations provided based on morphological characters of the adult female. A key to all known Ukrainian species of the genus is presented.